The Archive of Unnamed Workers/ Shadows - Stylianou-Lambert, Theopisti; Achilleos, Alexia (My University, 2023)
Theopisti Stylianou-Lambert & Alexia Achilleos The Archive of Unnamed Workers, 2022, GAN-generated images on 35mm glass photographic slides (reversal film), dimensions varied The Archive of Unnamed Workers attempts to negotiate the absences in archaeology-related photographic archives by creating numerous, fictional, portraits of Cypriot workers using Generative Adversarial Network (GAN) machine learning technology. Photographic archives by the Swedish Cyprus Expedition, John Linton Myres, and Luigi Palma di Cesnola, became the source material for these new, machine-made, portraits of Cypriot workers at archaeological sites. The final images are completely artificially created, and do not resemble any real workers. Instead, they pay tribute to the countless and unphotographed workers who contributed to Cypriot archaeology but who remain unnamed and unacknowledged. The artificial intelligence-generated portraits were subsequently transferred to 35mm glass photographic slides (reversal film), a technology widely used in the mid-20th century, which is almost obsolete today.